CONSOLIDATED STATEMENTS AND THE LAW. - Simon, Sidney I. (The Accounting Review, 1953)
Accounting and legal authorities insist that the law has materially influenced the development of accounting principles and practices, and that this influence has had profound and far reaching effects. Conversely, it has been asserted that accounting practice has done much, by developing the concept of the single entity of the group of affiliated companies, through the consolidated statement, in bringing about some legal recognition of these separate entities as a single operating unit. In conducting the legal investigation, the argument as to whether there are indeed any true principles of accounting is ignored, and an authoritative group of principles affecting the consolidated state merits is used, the acceptance of each by the profession as a recognized principle of accounting being individually shown. The treatment of each principle is then followed by a discussion of the court decisions that involve the application of each of the accounting tenets studied. This article does not generally attempt to analyze critically each of the cases cited to decide whether it enunciated what might be called good or bad law, in the light of the basic legal or accounting theories, rather the study accepts the decisions as it finds them, and merely attempts to determine the extent to which they approve or disapprove of the accounting principles involved in the particular cases.